ANALISIS TEGANGAN PADA TABUNG KOMPOSIT SERAT KARBON UNTUK MOTOR ROKET BERDIAMETER 200 MM DENGAN METODE SINGLE LAYER LAMINATED ELEMENT - Ronald Gunawan Putra,; Robertus Heru Triharjanto (Jurnal Teknologi Dirgantara, 2010)
This research analizes rocket RWX 200 motor tube using carbon fiber reinforced for 6 mm thickness in order to optimize the weight. Carbon fiber is chosen due to its mechanical properties such as high strength and stiffness, and high temperature resistance, as the specification needs of the rocket motor tube. Rocket motor tube is manufactured by using weaving method, while the analysis and simulation is calculated by assuming it as laminate with the [0/90]s stacking sequence. From the calculation and simulation, it is determined that the X stress component of the laminates is below the strength of the material, while the Y stress component is beyond the strength of the material. It can be concluded that 900 laminae in each laminates has been failed. Keywords: Composite tube, Finite element method, Rocket motor